2010
DOI: 10.2298/pif1002157r
|View full text |Cite
|
Sign up to set email alerts
|

Field efficacy of mandipropamid for the control of potato late blight

Abstract: SUMMARYThe efficacy of mandipropamid (Revus 250 SC) in controlling Phytophthora infestans in potato was evaluated in field trials. The efficacies of Revus 250 SC in comparison with standard fungicides Quadris (azoxystrobin) were tested in several localities in Serbia (Kasarske Livade, Valjevska Kamenica and Opovo) in 2007 and 2008. Both of the tested fungicides exhibited high efficacy in controlling potato late blight. The differencies in the efficacy of Revus 250 SC (96.3-99.2%) and Quadris (94.1-95.5%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It was first introduced in 1977, and has since been considered an important tool to protect grape and vegetable crops from oomycete pathogens of the Peronosporales order [2]. In practical applications, CYM effectively combats downy mildew diseases caused by Plasmopara viticola in grapevine cultures and late blight diseases triggered by Phytophthora infestans in tomato and potato crops [3,4]. Due to its weak persistence (half-life of a few days, depending on the conditions) and mobile nature (adsorption coefficient, KOC 39-238), CYM displays a relatively short period of activity when used alone [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was first introduced in 1977, and has since been considered an important tool to protect grape and vegetable crops from oomycete pathogens of the Peronosporales order [2]. In practical applications, CYM effectively combats downy mildew diseases caused by Plasmopara viticola in grapevine cultures and late blight diseases triggered by Phytophthora infestans in tomato and potato crops [3,4]. Due to its weak persistence (half-life of a few days, depending on the conditions) and mobile nature (adsorption coefficient, KOC 39-238), CYM displays a relatively short period of activity when used alone [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rekanović et al. (2010), Töfoli et al. (2016), and Fanigliulo and Sacchetti (2009) also reported that racemic mandipropamid was effective against potato late blight, potato early blight ( Alternaria solani ), and Phytophthora infestans on tomato ( Solanum lycopersicum L.), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Mandipropamid, the chemical structure of which is demonstrated in Supplemental Figure S1, is a new chiral carboxylic acid amide (CAA) fungicide with extremely high activity against plant oomycete pathogens such as P. viticola and P. infestans; this pesticide works to inhibit mycelial growth and sporulation by nhibiting cell wall synthesis (Blum et al, 2010). For example, Rekanović et al (2010), Töfoli et al (2016), and Fanigliulo and Sacchetti (2009) also reported that racemic mandipropamid was effective against potato late blight, potato early blight (Alternaria solani), and Phytophthora infestans on tomato (Solanum lycopersicum L.), respectively. After application, a large amount of mandipropamid could be absorbed in the cuticular wax layer, ensuring excellent rainfastness, which meant good persistence of its bioactivity (Fanigliulo & Sacchetti, 2009).…”
Section: Introductionmentioning
confidence: 99%